HUBUNGAN ANTARA CITRA MEREK DENGAN MINAT BELI HAND BODY LOTION PADA SISWA-SISWI KELAS XI DI SMA 2 CIPOCOK JAYA KOTA SERANG - Meilla Dwi Nurmala; Aria Mulyapradana; Meitami Sofiyanti (Institut Teknologi dan Bisnis Dewantara, 2020)
Teenagers are potential consumers for skin care products such as hand body lotion because in their teens they want to try new things. Seeing this phenomenon, the manufacturers of skin care products competing to captivate the hearts of consumers by growing a positive brand image to adolescents, causing interest in buying hand body lotion. Based on this, a hypothesis emerged that students tend to be interested in buying hand body lotion from brands with positive images. Therefore, the purpose of this study was to obtain a picture of the relationship between brand image and buying interest at students of SMAN 2 Cipocok Jaya, Serang City. The method used is quantitative by using SPSS version 12.0 and the method of data collection by observation, interviews and distributing questionnaires to students of Cipocok Jaya Serang City with 123 people. Data collection techniques using a questionnaire with a Likert scale, each of which has been tested using validity and reliability. The data analysis used a bivariate correlation analysis and hypothesis testing using the t test so that the results show that there is a positive relationship between brand image and buying interest in Class XI students of SMAN 2 Cipocok Jaya, Serang City, this is evidenced by the results of the correlation coefficient of brand image with buying interest (r) equal to 0.332 and p = 0,000 with p <0.05.